CD4+ T cell–independent DNA vaccination against opportunistic infections - Mingquan Zheng; Alistair J. Ramsay; Myles B. Robichaux; Karen A. Norris; Corrine Kliment; Christopher Crowe; Rekha R. Rapaka; Chad Steele; Florencia McAllister; Judd E. Shellito; Luis Marrero; Paul Schwarzenberger; et al. (The Journal of Clinical Investigation, 2005)
Depletion or dysfunction of CD4+ T lymphocytes profoundly perturbs host defenses and impairs immunogenicity of vaccines. Here, we show that plasmid DNA vaccination with a cassette encoding antigen (OVA) and a second cassette encoding full-length CD40 ligand (CD40L), a molecule expressed on activated CD4+ T lymphocytes and critical for T cell helper function, can elicit significant titers of antigen-specific immunoglobulins in serum and Tc1 CD8+ T cell responses in CD4-deficient mice. To investigate whether this approach leads to CD4+ T cell–independent vaccine protection against a prototypic AIDS-defining infection, Pneumocystis (PC) pneumonia, we used serum from mice vaccinated with PC-pulsed, CD40L-modifed DCs to immunoprecipitate PC antigens. Kexin, a PC antigen identified by this approach, was used in a similar DNA vaccine strategy with or without CD40L. CD4-deficient mice receiving DNA vaccines encoding Kexin and CD40L showed significantly higher anti-PC IgG titers as well as opsonic killing of PC compared with those vaccinated with Kexin alone. Moreover, CD4-depleted, Kexin-vaccinated mice showed a 3-log greater protection in a PC challenge model. Adoptive transfer of CD19+ cells or IgG to SCID mice conferred protection against PC challenge, indicating a role of humoral immunity in the protection. The results of these studies show promise for CD4-independent vaccination against HIV-related or other opportunistic pathogens.